Bullying Perpetration and Narcissistic Personality Traits across Adolescence: Joint Trajectories and Childhood Risk Factors - Farrell, Ann H.; Vaillancourt, Tracy (Frontiers in Psychiatry, 2020)
Objectives: Although there is some evidence on the longitudinal associations between bullying perpetration and narcissistic personality traits, their joint developmental trajectories across early to late adolescence are largely unknown. Accordingly, we examined the co-development of bullying perpetration and narcissistic personality traits across adolescence and examined the childhood predictors of these joint trajectories. Method: Self-reports of bullying and narcissistic personality traits were assessed across 6 years of adolescence from Grade 7 (i.e., age 13) to Grade 12 (i.e., age 18) in a sample of 616 Canadian adolescents and childhood predictors were assessed in Grades 5 and 6. Results: As predicted, latent class growth analyses demonstrated that most adolescents were reflected in a trajectory of low decreasing bullying (82.0%) and a smaller group followed a moderate stable trajectory of bullying (18.0%). The majority of adolescents followed a moderate stable trajectory of narcissistic traits (56.3%), followed by a high increasing trajectory of narcissistic traits (22.8%), and a low decreasing trajectory of narcissistic traits (20.9%). Six percent of adolescents followed a high-risk dual trajectory of moderate stable bullying and high increasing narcissistic traits (high-risk group). Also as predicted, higher hyperactivity, higher frustration, and lower anxiety in childhood differentiated the high-risk group from a low-risk group (low decreasing bullying and low decreasing narcissistic traits; 19.0%). Higher childhood hyperactivity also differentiated a group of adolescents who followed a trajectory of moderate stable bullying and moderate stable narcissistic traits (10.0%) from the low-risk group. Results showed that moderate stable bullying was a better indicator of high increasing and moderate stable trajectories of narcissistic personality traits than the reverse. Conclusions: Findings suggest adolescence is a time when personality and bullying reflect dynamic and heterogeneous development. Early intervention of childhood risk factors may help prevent a high-risk developmental course of bullying and narcissistic personality traits across adolescence.